2022
DOI: 10.3390/molecules27041232
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Antioxidant Activities of Bioactive Peptides Obtained from Cornus officinalis

Abstract: The present study is a preparation of bioactive peptides from Cornus officinalis proteins by the compound enzymatic hydrolysis method. Response surface methodology (RSM) coupled with Box–Behnken design (BBD) is used to optimize the preparation process of Cornus officinalis peptides. The effects of independent variables, such as the amount of enzyme, pH value, time, extraction times and the ratio of material to liquid on the yield of peptides, are also investigated. The analysis results of the RSM model show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…4 As a high-quality protein, the utilization rate of walnut protein is extremely low in China, and the protein content of walnut meal is up to 40% or more, from which the extraction of walnut protein can significantly increase the added value of the walnut industry. 5 Numerous studies have shown that walnut protein has significant antioxidant, 6 anti-inflammatory, 7 blood pressure-lowering, 8 and sleep-improvement 9 effects. In addition, according to Elouafy et al , 10 pyruvic acid, which is present in walnuts, has the ability to perform functions of dissolution, abatement and excretion, which has a good curative effect on gallstones; walnuts are rich in vitamin E, which has a function in cosmetology.…”
Section: Introductionmentioning
confidence: 99%
“…4 As a high-quality protein, the utilization rate of walnut protein is extremely low in China, and the protein content of walnut meal is up to 40% or more, from which the extraction of walnut protein can significantly increase the added value of the walnut industry. 5 Numerous studies have shown that walnut protein has significant antioxidant, 6 anti-inflammatory, 7 blood pressure-lowering, 8 and sleep-improvement 9 effects. In addition, according to Elouafy et al , 10 pyruvic acid, which is present in walnuts, has the ability to perform functions of dissolution, abatement and excretion, which has a good curative effect on gallstones; walnuts are rich in vitamin E, which has a function in cosmetology.…”
Section: Introductionmentioning
confidence: 99%